Audit of caesarean deliveries in a tertiary care hospital of northern Andhra Pradesh using modified Robson criteria - V., Prabhavathi; B., Krishnamma; V., Prasad D. K.; K., Bhavya; R., Satyavathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Today, there is an increased trend in the incidence of caesarean section (CS) rate worldwide particularly in India, even with the lack of evidence supporting considerable maternal and perinatal benefits with higher CS rates. The main objective of our study was to find the incidence of CS rate, auditing the data on the basis of modified Robson criteria, factors responsible for the most common group, to know the changing trends of CS and finally put forth the strategies to reduce CS rate. Methods: This is a retrospective study of 472 CS cases carried out in a tertiary care hospital during the year 2016. All the cases were grouped according to the modified Robson criteria and the data was analyzed. The data were grouped into 3 different slots of 4 months each (FF = first four months; MF = middle four months and LF = last four months of the year 2016). Results: A significant increasing trend was observed in the groups of 2B and 5C where as a significant decreasing trend was noticed in 6C and 7C. The most common indications for caesarean delivery were cephalo-pelvic disproportion (CPD) (28%) and fetal distress (22%) in group 1 whereas in group 2A CPD, fetal distress and failed induction were found to be 12%, 24% and 30% respectively. Conclusions: The change in trend has been noticed in the last few months particularly in 2B and 5C groups suggesting that there is a change in the attitude of obstetricians in conducting caesarean deliveries before the onset of labour rather than performing CS after the onset of labour. Targeting 2B along with 5C would help our efforts in reducing the CS rate.